KETAHANAN KELUARGA DI MASA PANDEMI COVID-19 MASYARAKAT DESA CISUMUR PRESPEKTIF SAKINAH - Annida fathiyah fauzan (Hukum Keluarga Islam, 2022)
The Covid 19 pandemic is a pandemic disaster that has hit the whole world, especially in Indonesia, the government's policy is to carry out social distancing and carry out partial regional quarantine to reduce restrictions on outside activities and minimize the transmission rate of the corona virus. This makes the situation in almost all aspects of life experience something new, especially in changes in food supply chain patterns so that the impact of the pandemic has also caused the country's economy to experience a very significant contraction, many formal sector workers have been affected by layoffs (PHK), entrepreneurs, companies , including many street vendors who have gone out of business. As happened in the Cisumur Gandrungmangu area, there are some women who work to help their husbands to maintain their families so that time with family and communication between families is also reduced. Therefore the author is interested in further researching how the condition of the Cisumur village community was during the pandemic and what efforts were made by the community to maintain family resilience. To examine the situation further, the researcher conducted direct interviews with the Cisumur village community to find out the condition of the village community. In conditions like this, it certainly greatly affects the situation of the family, especially at the economic level, so that there are many divorce cases of domestic violence. One important effort is to strengthen family resilience. Because if the husband and wife cannot strengthen family resilience, problems will arise in the household that will become increasingly worse. The following is the definition of sakinah mawaddah warahmah as provision in the family.